Determination of Knowledge Level of Working Women in the 15-49 Age Group on Family Planning and Related Factors (Turkey Health Literacy Journal, 2022)
One of the most important parameters of reproductive health is family planning. The effect of knowledge level is important in the effective use of family planning. Conducting research with different groups on this subject, identifying risk factors that will have negative effects on maternal and child health will contribute to future evaluations. In this study, it has been tried to contribute to the scientific literature by researching the knowledge level of working women, especially about family planning, and to create a new source for family planning regulations by developing new hypotheses on this subject. For this reason, it is aimed to determine the level of knowledge and related factors of working women in the 15-49 age group about family planning.